Can Intensity-Modulated-Radiotherapy Reduce Toxicity in Head and Neck Squamous Cell Carcinoma? - Julie van der Veen (Cancers, 2017)
Intensity modulated radiotherapy (IMRT) is a modern radiotherapy technique that was implemented in the mid-1990s. It allows closer shaping of dose, to target volumes, thereby sparing organs at risk (OARs). Before the IMRT-era, two-dimensional radiotherapy (2DRT) and later three-dimensional conformal radiotherapy (3DCRT) were the techniques of choice, but this robust way of irradiating caused more normal tissue to receive a higher dose. Radiation of cancers in the head and neck region is complex because of close proximity to critical normal tissue and the large target volumes that need to be treated at high doses. IMRT offers an elegant solution compared with 3DCRT and surgery because it allows organ preservation and improved function preservation. In this manuscript, we review the rationales for IMRT, with an emphasis on toxicity outcomes compared with 3DCRT. We performed a review of the literature and looked at the most important randomised controlled trials comparing IMRT with 3DCRT. We conclude that IMRT is safe in regard to disease outcome, and that it allows better sparing of normal tissue, thereby causing less toxicity, resulting in a smaller impact on quality of life compared with conventional radiotherapy in the treatment of head and neck cancer.